2006
DOI: 10.1007/s10653-005-9036-7
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contamination and Distribution in the Urban Environment of Guangzhou, SE China

Abstract: Ever-increasing heavy metal accumulation in the urban environment of Guangzhou, the largest light industrial production base and one of the most rapidly developing cities in China, poses a serious threat to environment as well as to human health in the region. As a sink or source, urban deposits are good indicators of the level and extent of heavy metal accumulation in the surface environment. The aim of this preliminary study was to examine the distribution of heavy metal contamination in the urban environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(69 citation statements)
references
References 27 publications
(42 reference statements)
3
64
1
1
Order By: Relevance
“…Many studies have focused on the elemental concentration of heavy metals and other contaminants (Al-Khashman, 2004;Apeagyei et al, 2011). Urbanization results in the deposition of pollutants and other toxic substances causing the degradation of environmental conditions (Duzgoren-Aydin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the elemental concentration of heavy metals and other contaminants (Al-Khashman, 2004;Apeagyei et al, 2011). Urbanization results in the deposition of pollutants and other toxic substances causing the degradation of environmental conditions (Duzgoren-Aydin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Different types of pollution sources produce RDS particles with a range of diameters. 7 Kobringer and Geinopolos (1984) reported that tire wear produces particles with an average diameter of 20 μm. Environmental Science & Technology ARTICLE Habibi (1973) found that 57% of the Pb emitted in vehicle exhaust was associated with particles >9 μm in diameter.…”
Section: ' Discussionmentioning
confidence: 99%
“…It is a common practice to compare mean concentrations of heavy metals in bus stations dusts in different urban environments (De Miguel et al 1997;Duzgoren-Aydin et al 2006;Lu et al 2009b;Li et al 2012;Xu et al 2015), although there are no universally accepted sampling and analytical procedures for geochemical studies of urban deposits. In table 2, concentrations of heavy metals measured in bus station dusts of Xifeng are compared with data reported for other cities streets dusts (Xu et al 2004;Guo et al 2005;Han et al 2006;Gao et al 2007;Shi et al 2008;Lu et al 2009a;Wei et al 2009;Zhang and Wang 2009;Li et al 2012;Shi et al 2013;Han et al 2014Han et al , 2016Liu et al 2014;Zhao et al 2016).…”
Section: Contamination Assessment Methodsmentioning
confidence: 99%
“…In general, each city has its own characteristics combination of elemental compositions, and the observed similarities as well as variations may not reflect actual natural and anthropogenic diversities among the different urban settings. Therefore, there is an immediate need to establish a standard procedure to represent and analyze urban samples (Duzgoren-Aydin et al 2006;Lu et al 2009b;Li et al 2012;Xu et al 2015). Enrichment factors of heavy metals were calculated for each bus station dusts sample relative to the background value of the elements in Chinese soil (CNEMC, 1990), choosing Al as the reference element.…”
Section: Contamination Assessment Methodsmentioning
confidence: 99%